BUREAUCRATIC TRANSFORMATION THROUGH PUBLIC SERVICES INNOVATION BASED ON BREXIT BRAILLE FOR DISABILITIES IN MALANG CITY - Muhammad Kamil (POLITICO, 2021)
Bureaucratic innovation is the government's commitment to improving public services in building a good pactice in government institutions. This study aims to analyze the transformation of bureaucracy through public service innovations for disabilities in Malang City. The research method in this study uses a qualitative descriptive approach with primary and secondary data sources. The data collection used the method of observation, interviews, and documentation. While the data analysis technique in this study uses the method developed by Creswell, specifically processing and interpreting data, reading the entire data, coding, describing categories and themes, and checking the accuracy of research results for drawing conclusions. The concept in this study uses Bureaucratic Transformation and New Public Service, which is to  that the bureaucracy has the responsibility and obligation to provide services to the community without discrimination to community as well as an innovative government thdigitalization era. The results in this study are, (1) New Directions for System and Human Resources Transformation in public services; An important premise in the transformation of the bureaucracy and public services is a sense of belonging. In realizing public services for people with disabilities in Malang City, Public Health Agency and Janti Public Health Center have improved the quality of public services and built a government practice of innovation. Janti Public Health Center is a companion organization that has provided breakthrough steps to facilitate services for disabled groups. (2) The exclusivity and innovation of public services; The paradigm shift towards the governance process has no significant effect on the provision of good public services.